Cyclic bend tests for the reliability evaluation of printed circuit boards under dynamic loads - Z. Major; P.F.Fuchs (Fracture and Structural Integrity)
The reliability of printed circuit boards under dynamic loads is a key issue in the handheld electronic products industry. In order to predict the performance of the boards in their application lifetime, different tests were developed. The current industry-wide standard testing method is a board level drop test. In this test, the boards are dropped under defined conditions until a failure in the board is detected. The main failure driver is a flexural oscillation of the board due to the impact event. As this test method has a number of drawbacks, an alternative test method was evaluated in this study. A board level cyclic bend test was used and the results of both tests were compared. A very good correlation between the methods could be observed, supporting the suitability of the board level cyclic bend test for the determination of the drop test performance. The advantages of the alternative test method were shorter testing times, better adaptability and test simulations at lower computing time. In future analysis, test simulations will be used to generate Wöhler curves related to the local stresses.